Exploration of techno-functional properties and metabolomic profile of Scleroderma texense (Phutuki Mushroom): a comparative study with Agaricus bisporus (white button mushroom) - Arun Kumar Gupta; Avinash Kumar Jha; Bindu Naik; Vijay Kumar; Sarvesh Rustagi; Milad Tavassoli (Discover Food)
Abstract Mushrooms are crucial in the food and nutraceutical industries for their unique nutritional profile and versatile culinary applications. Despite numerous wild varieties offering substantial health benefits, they are underutilized. This study aims to comprehensively analyze Agaricus bisporus (AB) and Scleroderma texense (ST) to understand their distinct characteristics, aiding food processors in making informed ingredient decisions. Engineering properties of fresh mushrooms revealed significant variations. AB exhibited larger dimensions and lower moisture content compared to ST. Proximate analysis of mushroom flour indicated that AB possessed higher fat content (23.89%), energy and calorie value while ST inner mass had highest protein content (23.75%) compared to ST coat. ST coat demonstrated highest crude fibre content than AB along with superior flow and packing properties compared to AB and ST inner mass. Dried mushrooms had a shrunken strides-like structure, as observed by SEM. The levels of K, Ca, Fe, P, and Mg were significantly higher in ST than in AB, marking the first study to report the elemental composition of ST as revealed by EDX. Results obtained from FTIR revealed the presence of functional groups associated with fat (1740 cm−1), protein (1560 cm−1), polysaccharides (1500–750 cm−1), and moisture (3300 cm−1) in mushroom samples. AB had a higher total phenolic content (5.49 mg GAE g−1) and DPPH free scavenging activity (68.07%), while ST, demonstrated superior total flavonoid content (4.66 mg QE g−1) and ABTS scavenging activity (87.69%). The outcomes of this study offer a wealth of information that can be leveraged by food scientists, product developers, and the food industry as a whole. Graphical Abstract